Assessment of Acoustic Pulse Technology (APT-X) in the treatment of Mastitis in Indian Dairy Cows – A Multicentered Trial compared to standard Antibiotic Treatment - Gabriel Leitner; D. N. Hegde; Vikas Gupta; Ragothaman S; Narendrakumar R (The Indian Veterinary Journal, 2023)
India is the world’s largest milk-producing country, with a 20% share in global production (OECD 2019) with over 193 million cattle .In India cattle are sacred, thus many states do not permit the slaughter of dairy cattle for meat production (Sharma et al., 2019). Mastitis, the inflammation of the mammary gland, is the single most important factor that imposes economic burdens on dairy farms worldwide (Halasa et al., 2007). Estimations show that 30% of dairy cattle are affected in both forms of mastitis infection, i.e., clinical (CM) and subclinical (SCM), and it is the most common reason for using antibiotics in dairy cows as preventive and treatment measures (Halasa et al., 2007; Pol and Ruegg, 2007; Saini et al. 2012). Antibiotics have been used to treat bovine mastitis for more than half a century, however, the effectiveness, financial aspects and long-term effects are debatable. Growing awareness of spread of antimicrobial-resistant (AMR) bacteria are influencing the decision-making progress of reducing antibiotics used in livestock production (Economou and Gousia, 2015; Magouras et al., 2017). Therefore, judicious use of mastitis antibiotics treatment should be evidence-based (Pyörälä, 2009).Continued use of antibiotics in the treatment and prevention of mastitis has a direct effect on fostering AMR, which has hazardous consequences on human health (Sawant et al., 2007). Moreover, antibiotics might weaken the cows’ immune system, making it more susceptible to repeated infections (Bradley et al., 2007; Enli et al., 2019).